2019
DOI: 10.1002/pan3.10065
|View full text |Cite
|
Sign up to set email alerts
|

Landowner functional types to characterize response to invasive forest insects

Abstract: Invasive forest insects can induce tree mortality in two ways: (a) by directly harming trees; or (b) by influencing forest owners to pre‐emptively harvest threatened trees. This study investigates forest owners’ intentions to harvest trees threatened by invasive insects. Our first objective is to identify and characterize agent functional types (AFTs) of family forest owners in the northeastern United States using a set of contingent behaviour questions contained in a mail survey. We establish AFTs as a form o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In the context of this study, “ash species” includes white ash ( Fraxinus americana ), green ash ( Fraxinus pennsylvanica ), and black ash ( Fraxinus nigra ). We considered privately owned plots only (omitting federal and state plots) to contextualize our findings within the discussion of private landowner behavior (e.g., Holt et al, 2020; MacLean et al, 2020; Markowski‐Lindsay et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In the context of this study, “ash species” includes white ash ( Fraxinus americana ), green ash ( Fraxinus pennsylvanica ), and black ash ( Fraxinus nigra ). We considered privately owned plots only (omitting federal and state plots) to contextualize our findings within the discussion of private landowner behavior (e.g., Holt et al, 2020; MacLean et al, 2020; Markowski‐Lindsay et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Some insects cause changes in forest type by eliminating specific tree species (Lovett et al, 2016). Human responses to insect outbreaks may amplify their effects, as many landowners choose to harvest forests threatened by insects (Foster & Orwig, 2006; Holt et al, 2020). Logging may result in larger changes to forest structure and composition, and greater aboveground carbon loss than insect damage alone, as timber harvests result in more abrupt mortality, remove large logs rather than leaving dead trees on‐site, remove additional nonhost tree species, and can cause disturbance to the forest floor (MacLean et al, 2020; Markowski‐Lindsay et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous attempts to understand management behavior and decades of interventions trying to influence family forest owners (Silver et al, 2015;Thompson et al, 2017). Several studies argue that family forest owners should be divided into typologies based on their reasons for owning land and behavioral responses (Majumdar et al, 2008;Goyke et al, 2019;Holt et al, 2020). In terms of specific management predictions, Thompson et al (2017) found that the largest predictors of harvesting behavior among family forest owners in the Northeastern US were not related to the characteristics of landowners themselves, but rather geographical factors such as distance to roads or biological factors such as basal area and forest type.…”
Section: Introductionmentioning
confidence: 99%